Ekho nedeli . Ekho nedeli . Echoes of the Week . Эхо недели - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Inflation in Russia; Presidential moratorium on increases to welfare payments; the state monopoly on alcohol production; foreign banks' activities in Russia. Featured in the program: Borovoi, Konstantin Natanovich (Entrepreneur); Lobov, Oleg Ivanovich (Minister of Economy of the Russian Federation) Contributors: Degtiarenko, Evgenii (Anchor) Инфляция в России; мораторий президента на увеличение социальных выплат; государственная монополия на алкогольную продукцию; деятельность иностранных банков в России. В программе участвуют: Боровой, Константин Натанович (Предприниматель ); Лобов, Олег Иванович (Министр экономики Российской Федерации) Создатели: Дегтяренко, Евгений (Ведущий/Ведущая)